Pengaruh penambahan tepung kemangi (Ocimum basilicum) terhadap komposisi kimia dan kualitas fisik ayam broiler - Adelina Ari Hamiyanti; B. Sutomo; A. F. Rozi; Y. Adnyono; R. Darajat (Faculty of Animal Science, Universitas Brawijaya, 2013)
The study tended to examine Kemangi meal (Ocimum basilicum) addition on chemical composition and physical quality of broiler meat. The materials of the study were 150 DOC (Phokphand CP 707 strain). The method of the study was Completely Randomized Design with 5 treatments and 3 replications. The treatments were the addition of kemangi meal in broiler feed at various levels such as 0% (P0), 0.50% (P1), 0.75% (P2), 1.00% (P3), and 1.25% (P4). The variables were protein, fat, cholesterol, pH, water holding capacity and cooking loss of broiler meat. The data were analyzed by analysis of variance and if there were significant differences, the Least Significance Different Test (LSD) would be applied. The study showed that kemangi meal addition had a highly significant effect (P<0.01) on meat protein, fat, cholesterol, WHC, pH and on cooking loss (P<0.05). The stuy concluded that the addition of kemangi meal could improve chemical composition and physical quality of broiler meat. Keywords: kemangi, protein, fat, cholesterol, pH, water holding capacity, cooking loss